Pelatihan Kesiapsiagaan Bencana kepada Peserta Didik SMA Muhammadiyah 1 Palangka Raya - Irwani Irwani; Rachmat Hidayat (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The people of Palangka Raya city, especially millennials, especially students who are currently a small part of the Indonesian population who are prone to disasters and are responsible for maintaining the local wisdom of the Indonesian people in the face of disasters. It is these millennials who must receive disaster preparedness training in order to reduce the impact of a bigger disaster. Solutions that can be given to increase public knowledge, especially millennials, about disaster management and preparedness to reduce the more significant impact of disasters occur, namely by providing training to students of SMA Muhammadiyah 1 Palangka Raya.